2017
DOI: 10.1016/j.bmc.2017.07.041
|View full text |Cite
|
Sign up to set email alerts
|

Chemoselective fluorination and chemoinformatic analysis of griseofulvin: Natural vs fluorinated fungal metabolites

Abstract: Griseofulvin is a fungal metabolite and antifungal drug used for the treatment of dermatophytosis in both humans and animals. Recently, griseofulvin and its analogues have attracted renewed attention due to reports of their potential anticancer effects. In this study griseofulvin (1) and related analogues (2–6, with 4 being new to literature) were isolated from Xylaria cubensis. Six fluorinated analogues (7–12) were synthesized, each in a single step using the isolated natural products and Selectflour, so as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…Finally, the coupling constants ( J CF ) for 13 C– 19 F are quite large (up to 250 Hz), providing information about the location of the F atom and the connectivity of adjacent atoms 278,285. In fact, these large J CF couplings are very helpful in structure elucidation, akin to using HSQC data to assign how a 13 C signal can be correlated with its attached 1 H signals 280,286. Additionally, relatively simple experiments, such as a 1 H decoupled 13 C experiment, will display splitting due to the 13 C– 19 F coupling, and upon first inspection, such data may be quite foreign, especially to a student.…”
Section: Other Nucleimentioning
confidence: 99%
“…Finally, the coupling constants ( J CF ) for 13 C– 19 F are quite large (up to 250 Hz), providing information about the location of the F atom and the connectivity of adjacent atoms 278,285. In fact, these large J CF couplings are very helpful in structure elucidation, akin to using HSQC data to assign how a 13 C signal can be correlated with its attached 1 H signals 280,286. Additionally, relatively simple experiments, such as a 1 H decoupled 13 C experiment, will display splitting due to the 13 C– 19 F coupling, and upon first inspection, such data may be quite foreign, especially to a student.…”
Section: Other Nucleimentioning
confidence: 99%
“…To obtain baseline data, the monoculture of X. cubensis was sampled by droplet probe, and the LC-MS base peak chromatogram only showed two peaks, which corresponded to griseofulvin ( 8 ) and dechlorogriseofulvin ( 9 ) as determined by comparison of accurate mass and RT of a standard (El-Elimat et al, 2013; Paguigan et al, 2017). Griseofulvin ( 8 ) and dechlorogriseofulvin ( 9 ) were present in multiple spots across the mycelium, with both more concentrated at the mycelial edge.…”
Section: Resultsmentioning
confidence: 99%
“…The fungal growth was extracted and purified to isolate compounds that were characterized. In the co-culture griseofulvin ( 8 ) and dechlorogriseofulvin ( 9 ) (Paguigan et al, 2017), which were present in the monoculture, were isolated, as were the two analogs 5′-hydroxygriseofulvin ( 10 ) and dechloro-5′-hydroxygriseofulvin ( 11 ) (Paguigan et al, 2017), which were not observed in monoculture (Supplementary Figures S12–S15). The mycotoxins cytochalasin D ( 12 ) (Jikai et al, 2002), cytochalasin Q ( 13 ) (El-Elimat et al, 2013), cytochalasin C ( 14 ), zygosporin E ( 15 ) (Vedejs et al, 1988; Edwards et al, 1989), and 7- O -acetylcytochalasin B ( 16 ) (Capasso et al, 1991), (Figure 7) were observed in monoculture, albeit at extremely low concentrations that did not afford structural characterization.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations